Osteoprotegerin regulates cancer cell migration through SDF-1/CXCR4 axis and promotes tumour development by increasing neovascularization. (1st June 2017) - Benslimane-Ahmim, Zahia; Pereira, Jessica; Lokajczyk, Anna; Dizier, Blandine; Galy-Fauroux, Isabelle; Fischer, Anne-Marie; Heymann, Dominique; Boisson-Vidal, Catherine
Abstract: We previously reported that OPG is involved in ischemic tissue neovascularization through the secretion of SDF-1 by pretreated-OPG endothelial colony-forming cells (ECFCs). As the vascularization is one of the key factor influencing the tumour growth and cancer cell dissemination, we investigated whether OPG was able to modulate the invasion of human MNNG-HOS osteosarcoma and DU145 prostate cancer cell lines in vitro and in vivo . Cell motility was analysed in vitro by using Boyden chambers. Human GFP-labelled MMNG-HOS cells were inoculated in immunodeficient mice and the tumour nodules formed were then injected with OPG and/or FGF-2, AMD3100 or 0.9% NaCl (control group). Tumour growth was manually followed and angiogenesis was assessed by immunohistochemistry. In vitro, SDF-1 released by OPG-pretreated ECFCs markedly attracted both MNNG-HOS and DU145 cells and induced spontaneous migration of cancer cells. In vivo, tumour volumes were significantly increased in OPG-treated group compared to the control group and OPG potentiated the effect of FGF-2. Concomitantly, OPG alone or combined with FGF-2 increased the number of new vasculature compared to the control group. Interestingly AMD3100, an inhibitor of SDF-1, prevented the in vivo effects of OPG induced by SDF-1 This study provides experimental evidence that OPG promotes tumour development trough SDF-1/CXCR4 axis. Highlights: OPG promotes tumour development. OPG is actively involved in tumour revascularization. SDF-1 released by OPG-pretreated endothelial colony-forming cells chemoattract cancer cells. SDF-1 induces spontaneous migration of osteosarcoma and carcinoma cell lines. OPG promotes tumour development trough SDF-1/CXCR4 axis.